2008
DOI: 10.1007/s00439-008-0576-7
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia and pancytopenia caused by a mutation in TINF2

Abstract: The syndrome of ataxia-pancytopenia is an autosomal dominant disorder characterized by cerebellar ataxia, peripheral neuropathies, pancytopenia and a predilection to myelodysplastic syndrome and acute myeloid leukemia. The genetic basis of this condition is unknown. We describe a child who presented with ataxia and pancytopenia and was found to have a heterozygous mutation, c.845G>A (Arg282His) in TINF2, a gene recently reported to be mutated in a subset of patients with autosomal dominant dyskeratosis congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…In addition to DC, mutations of TINF2 were also identified in patients with other diseases associated with bone marrow failure (e.g. ataxia-pancytopenia and aplastic anemia) (6,21,22).…”
mentioning
confidence: 99%
“…In addition to DC, mutations of TINF2 were also identified in patients with other diseases associated with bone marrow failure (e.g. ataxia-pancytopenia and aplastic anemia) (6,21,22).…”
mentioning
confidence: 99%
“…These facts suggested that TGM6 may be a pathogenic factor for both familial AML and SCA; and there have been numerous reports of mutations of one gene causing a disease with a wide range of symptoms including ataxia and blood malignancies, such as ATM mutations causing ataxiatelangiectasia, 27 and TERC/TERT mutations causing dyskeratosis congenital. 28 In fact, two members of TGM family, TGM2 and FXIII-A, 16 have been recognised as pleiotropy genes and can affect multiple traits. So we suggest that TGM6 may be another pleiotropy gene, and contribute to both ataxia and leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…(187) Telomeropathies, a disorder caused by defects in the telomere maintenance machinery, just recently discovered shared a constellation of overlapping syndromes. (188,189) DKC was the first disorder associated to telomerophaty, manifest the diagnostic triad of oral leukoplakia, skin hyperpigmentation, nail dystrophy (190)(191)(192), most prominent display organ failure, usually in the bone marrow and a seri of symptoms that less frequently appear such as aplastic anemia or specific lymphopenias. (193,194) In adulthood, idiopathic pulmonary fibrosis (IPF) is the most common symptom of a telomeropathy.…”
Section: Telomeres and Diseasesmentioning
confidence: 99%